Detachment and sonoporation of adherent HeLa-cells by shock wave-induced cavitation - Ohl, Claus-Dieter; Wolfrum, Bernhard (Biochimica et biophysica acta, 2003)
The interaction of lithotripter-generated shock waves with adherent cells is investigated using high-speed optical techniques. We show that shock waves permeabilize adherent cells in vitro through the action of cavitation bubbles. The bubbles are formed in the trailing tensile pulse of a lithotripter-generated shock wave where the pressure drops below the vapor pressure. Upon collapse of cavitation bubbles, a strong flow field is generated which accounts for two effects: first, detachment of cells from the substrate; and second, the temporary opening of cell membranes followed by molecular uptake, a process called sonoporation. Comparison of observed cell detachment with results from a theoretical model considering peeling cell detachment by a wall jet-induced shear stress shows reasonable agreement.